Ответ:
-0.5 или -1/2
Пошаговое объяснение:
убираем скобки и решаем выражение
Пошаговое объяснение: = -2/6+(-1/6)+(-1 5/6)+2 1/2= (-3/6)+(-1 5/6)+2 1/2=
-1/2+2 1/2+(- 1 5/6)=2- 1 5/6=1 6/6- 1 5/6=1/6.
или т.о.
-2/6+(-1/6)+(-1 5/6)+2 1/2= -1 8/6+2 3/6= - 2 2/6+2 3/6=1/6.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
-0.5 или -1/2
Пошаговое объяснение:
убираем скобки и решаем выражение
Ответ:
Пошаговое объяснение: = -2/6+(-1/6)+(-1 5/6)+2 1/2= (-3/6)+(-1 5/6)+2 1/2=
-1/2+2 1/2+(- 1 5/6)=2- 1 5/6=1 6/6- 1 5/6=1/6.
или т.о.
-2/6+(-1/6)+(-1 5/6)+2 1/2= -1 8/6+2 3/6= - 2 2/6+2 3/6=1/6.